Fjellrev i Finnmark : forskning og tiltak 2005 - Skog, E.; Ims, Rolf Anker; Killengreen, Siw Turid; Scheie, J. O.; Yoccoz, Nigel Gilles; Mørk, T.; Langeland, K.; Henden, John-André; Ravolainen, Virve (Universitetet i Tromsø, 2005)
Faglig årsrapport for 2005 til DN.